Attitudes and opinions of counselors about education of gifted students - Nisa Gökden Kaya; Hasan Said Tortop (International Journal of Evaluation and Research in Education (IJERE), 2020)
Counselors play effective roles not only in diagnosing but also in education of gifted students who lead the development of the societies. This study aimed to examine the attitudes and opinions of the counselors about the education of the gifted students. In the study, descriptive survey model is used. Both qualitative and quantitative data was collected within mixed method, according to the principles of pragmatist philosophy. “Attitude Scale towards Gifted Education” was applied to 250 counselors in order to collect quantitative data. The scale, which consists of 14 items, was developed by Gagné and Nadeau and adapted to Turkish by Tortop. The qualitative data was collected by semi-structured interview form consists of four questions about opinions on education of gifted students in Turkey, and was applied to 40 counselors. The mean of scores gathered from “Attitude Scale towards Gifted Education” was found 3.6 which is evaluated as slightly positive attitude. The scores were analyzed according to gender, seniority, having gifted students and institution of counselors, by using t test and ANOVA. Content analysis was performed for qualitative data that was gathered from interviews. The majority of counselors have stated that there are problems in education and diagnosis of gifted students.